Planʺ vkhoda vʺ bukhtu Lakhtu na Onezhskomʺ ozeri︠e︡ sostavleni︠e︡ po sʺëmki︠e︡ 1879 goda / Izdani︠e︡ Gidrograficheskimʺ Departamentomʺ M. M. 1881 g. - Russia. Gidrograficheskīĭ departament; (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1881)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; "Masshtabʺ (200 sazh. vʺ di︠u︡ĭmi︠e︡)." [Scale 200 sazhens in 1 inch].; "No. 184" -- handwritten bottom right margin Grayscale; 1:14,000